(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2015)
Universities offer graduate programs in education (both master and doctoral) that prepare people for peace education, peaceful schools, social justice, and conflict management, resolution, and transformation. This paper is about the possibility of a stewardship paradigm being adopted into these mainstream graduate programs. It was prompted by personal reflections about what paradigm is behind the label Master’s degree? What does the word master connote? What would a steward’s degree look like, and how would one go about convincing mainstream graduate education of its merit? How would people react if they encountered someone in Education with an SED or SAED rather than a MED or MAED (with the A referring to a degree with a thesis)? Indeed, why do people call the product of graduate school a thesis, instead of a synthesis? Acknowledgment: An earlier version of this paper was published in the 2007 Culture of Peace Online Journal, 3(1), 5-10.